How to deal with the US financial crisis at no cost to the taxpayer - Claude Hillinger (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2008)
I discuss briefly the crisis itself and then give some criteria that should be used in evaluating any policy proposed o deal with it. This is followed by a critical discussion of some of the policy measures that have been suggested. Finally, I give a list of proposals, that I believe best satisfy the stated criteria. In contrast to almost all of the proposals that have been made, mine involve no bailout of the financial sector with public funds.
urn:nbn:de:bvb:19-epub-6929-0
Keywords: 330; financial crisis; Subprime-Krise; Finanzkrise; Bankenkrise; Wirtschaftspolitik; USA